DNA accumulation and transfer within an operational forensic exhibit storeroom. (January 2023) - Mercer, Claire; Taylor, Duncan; Henry, Julianne; Linacre, Adrian
Abstract: The increased sensitivity of current DNA profiling technologies allows the detection of trace amounts of DNA. With these advancements, there is an increased probability of detecting trace levels of DNA from contamination. Studies which investigate the accumulation and transfer of DNA within forensic laboratories provide insight into the possible mechanisms which may result in the contamination of exhibits. To gain a greater understanding of the level of DNA transfer between exhibit packaging and forensic workspaces, the accumulation of DNA within an operational forensic exhibit storeroom was investigated. Samples were collected from previously cleaned forensic exhibit storeroom shelves at various time points over a 14-week period. To determine the source of accumulating DNA, profiles generated from shelf samples were compared to the laboratory staff elimination database and the profiles generated from exhibits stored on each of the shelves sampled over the course of the study. Additionally, all samples were compared using STRmix™ mixture-to-mixture profile analysis, to identify the presence of common non-staff DNA donors and DNA from exhibits stored on the shelves sampled. As sampling time intervals increased, there was a significant increase in DNA quantity (ng) and number of profile contributors. The shelf height was also observed to influence the number of profile contributors, with higher numbers of contributors being found on lower shelves. DNA profiles generated from the shelf samples were matched to DNA from forensic staff members who enter the storeroom and police employees, who do not enter the storeroom. There were three instances where a common DNA profile contributor was identified between a shelf sample and the profile generated from an exhibit.This study provides insight into whether current exhibit storage procedures are still adequate given the highly sensitive DNA profiling systems currently used. Highlights: Highest DNA quantities and numbers of profile contributors were observed in samples taken at increased time intervals. DNA from forensic staff and police employees was observed to accumulate within the exhibit storeroom. Common profile contributors were observed between shelf samples and samples taken from exhibits stored within the storeroom.